2020
DOI: 10.3389/fimmu.2020.01775
|View full text |Cite
|
Sign up to set email alerts
|

Monogenic Inflammatory Bowel Disease: It's Never Too Late to Make a Diagnosis

Abstract: and interleukin (IL)-10 secretion. Finally, we show marked oligoclonal expansion of specific Band T-cell clones in the peripheral blood of the LRBA-deficient patient. Conclusions: LRBA deficiency is characterized by marked immunological changes in innate and adaptive immune cells. This case highlights the importance of advanced genetic studies in patients with a unique phenotype, regardless of their age at presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Consequently, in many of these diseases intestinal inflammation is accompanied by an immunodeficiency state, manifesting as recurrent or atypical infections. Identification of a monogenic disorder can have a marked impact on care provided for these patients through the possibility of providing targeted therapies, as we and others have shown before with anakinra for patients with IL10 receptor mutations (7) and abatacept for LPS Responsive Beige-Like Anchor Protein (LRBA) deficiency (8).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in many of these diseases intestinal inflammation is accompanied by an immunodeficiency state, manifesting as recurrent or atypical infections. Identification of a monogenic disorder can have a marked impact on care provided for these patients through the possibility of providing targeted therapies, as we and others have shown before with anakinra for patients with IL10 receptor mutations (7) and abatacept for LPS Responsive Beige-Like Anchor Protein (LRBA) deficiency (8).…”
Section: Introductionmentioning
confidence: 99%
“…It can represent the underpinning immune defect in cases of inflammatory bowel disease or autoimmune enteropathy with very-early onset (11,17,18). Histological features may include colonic crypt epithelium injury, chronic inflammation with remarkable increase of lymphocytes in the lamina propria and lymphocytic duodenitis resembling celiac disease (11,19,20). In our case, the main gastrointestinal complaint was a refractory erosive gastritis, without significant involvement of the remainder of the bowel apart from a lymphocytic duodenitis with villous atrophy, reminiscent of celiac disease.…”
Section: Discussionmentioning
confidence: 70%
“…With this report we would stress the importance of prompt investigations for genetic immune dysregulation disease in children with early onset gastroenterological autoimmune disorders, as recommended by several studies (20,29,35). The simultaneous presence of autoimmune FIGURE 4 | Mechanism of action of abatacept in LRBA deficiency.…”
Section: Discussionmentioning
confidence: 93%
“…LRBA, a member of the BEACH-WD40 protein family, is essential for immune function. It had a role in regulating cell surface expression of CTLA4, a key inhibitor of T-cell activation and proliferation ( Vardi et al, 2020 ). Further functional enrichment analyses showed that these co-expressed genes were primarily involved in metabolism of RNA, immune system process, ncRNA processing, regulation of cell cycle, E2F pathway and transcriptional regulation by TP53.…”
Section: Discussionmentioning
confidence: 99%